Chemical modifications of nucleic acid drugs and their delivery systems for gene‐based therapy. Issue 3 (5th January 2018) - Chen, Changmai; Yang, Zhenjun; Tang, Xinjing
Abstract: Gene‐based therapy is one of essential therapeutic strategies for precision medicine through targeting specific genes in specific cells of target tissues. However, there still exist many problems that need to be solved, such as safety, stability, selectivity, delivery, as well as immunity. Currently, the key challenges of gene‐based therapy for clinical potential applications are the safe and effective nucleic acid drugs as well as their safe and efficient gene delivery systems. In this review, we first focus on current nucleic acid drugs and their formulation in clinical trials and on the market, including antisense oligonucleotide, siRNA, aptamer, and plasmid nucleic acid drugs. Subsequently, we summarize different chemical modifications of nucleic acid drugs as well as their delivery systems for gene‐based therapeutics in vivo based on nucleic acid chemistry and nanotechnology methods.